Revenue analysis of the impact of the fee for issuing a permitforthe sale of alcohol on the commune budget on the example of selected coastal communes - Cezary Szydłowski (Financial Internet Quarterly, 2020)
The article presents an analysis of the level of income flowing to the municipalitiesb́udget from the permit fees to sell alcoholic beverages in selected municipalities. For the purposes of the article, three objectives have been set for determining the level of revenue from the fee. Particular objectives included establishing the share of the revenue from the fee in the total revenue of communes, the dynamics of changes in revenue in particular years and a general assessment of the dynamics of revenue from the fee in communes in relation to the base year. The study for the purpose of publication covered a total of 13 coastal communes (8 urban communes and 5 rural communes) from Pomorskie Voivodship in Poland in 2016-2019. The evaluation was carried out on the basis of available reports on the implementation of the commune budget and reports on the revenue of communes. Analytical methods were used.The results of the evaluation indicate that the income from the permit fees to sell alcoholic beverages constitutes a small share in the total income of the examined communes.
Keywords: H71; H83; 330; audit; budget revenues; local tax; public finance; local government; the fee for issuing a permit for the sell alcohol